Камолот тизимида психологик ҳимоя (назарий ёндашув) (SCIENCE and SOCIETY, 2018)
Psychological protection serves to overcome the psychological discomfort of the individual and is divided into basic and acquired psychological defenses. Psychological protection manifests itself in a certain form of behavior, and its essence is deter- mined by the presence of psychological culture and life experience, including the successful socialization of the subject.